Sistem Pendukung Keputusan Pemilihan Pengajar Les untuk Siswa Lembaga Bimbingan Belajar Dengan Metode Simple Additive Weight - Felix, Kendrick; Mettalia, Maitriyana; Sabatini, Tiffany; Itan, Vincent (Fakultas Komputer - Universitas Universal, 2024)
The goal of education is to help students develop their potential for personal, societal, and national benefits through an organized learning process between teachers and students. Through one-on-one or group tutoring sessions, tutoring centers are essential in helping students overcome scholastic obstacles and advance their abilities. Nevertheless, a lot of tutoring facilities, including